Answer:
z = 5*(1/2)
z = 5/10
---
time switching classes:
w = 7/10
---
y - 6x - z - w = 0
6x = y - z - w
x = (y - z - w)/6
x = (76/10 - 5/10 - 7/10)/6
x = (76 - 5 - 7)/(10*6)
x = (64)/(10*6)
x = (2*2*2*2*2*2)/(2*5*2*3)
x = (2*2*2*2)/(5*3)
x = 16/15
x = 1.0666666666
---
check:
y = 7 + 3/5
y = 7.6
z = 1/2
z = 0.5
w = 7/10
w = 0.7
y - 6x - z - w = 0
6x = y - z - w
x = (y - z - w)/6
x = (7.6 - 0.5 - 0.7)/6
x = 1.0666666666
---
answer:
z = 5*(1/2)
z = 5/10
---
time switching classes:
w = 7/10
---
y - 6x - z - w = 0
6x = y - z - w
x = (y - z - w)/6
x = (76/10 - 5/10 - 7/10)/6
x = (76 - 5 - 7)/(10*6)
x = (64)/(10*6)
x = (2*2*2*2*2*2)/(2*5*2*3)
x = (2*2*2*2)/(5*3)
x = 16/15
x = 1.0666666666
---
check:
y = 7 + 3/5
y = 7.6
z = 1/2
z = 0.5
w = 7/10
w = 0.7
y - 6x - z - w = 0
6x = y - z - w
x = (y - z - w)/6
x = (7.6 - 0.5 - 0.7)/6
x = 1.0666666666
---
answer:
each class is 1.07 hours
Step-by-step explanation:
Answer:
The solution is (0, 4)
Step-by-step explanation:
Please pay attention to the first two equations and drop the last two:
12x−5y=−20 y=x+4 x=x=x, equals y=y=y should ideally be:
12x−5y=−20
y=x+4
Let's find x. Substitute x + 4 for y in the first equation, obtaining:
12x - 5(x + 4) = -20
Carrying out the indicated multiplication, we get:
12x - 5x - 20 = -20, or 7x = 0
If x = 0 then y must be 0 + 4, or 4.
The solution is (0, 4)
There is no picture or anything but it’s ok .
Answer:
2ft
Step-by-step explanation:
5 x 10=50
7 x 12= 84
5+2=7 and 10+2=12